Huajuxiaoji Formula Alleviates Phenyl Sulfate-Induced Diabetic Kidney Disease by Inhibiting NLRP3 Inflammasome Activation and Pyroptosis - Zeng Zhang; Yueping Bi; Fengzhu Zhou; Duanchun Zhang; Siyu Xu; Xinyi Zhang; Zhaohua Fan; Zheng Yao; Yanming He (Journal of Diabetes Research)
Conclusions: Generally, HJXJ has the potential to reduce DKD injury and exerts anti-DKD effects by inhibiting the NLRP3-mediated NLRP3 inflammasome activation and pyroptosis in vitro and in vivo.